German Centres of Corporate Dominance and Recent Relocations of Corporate Headquarters - Brezina, Florian; Tyll, Ladislav; Sobíšek, Lukáš, 1983-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The purpose of this thesis is to identify the centres of corporate dominance in Germany and it is an attempt to describe the motives and main drivers of recent headquarter relocations within the country. The analysis is based on literature review, a database comprising the 10,000 largest companies in Germany and additional research for qualitative input to support the interpretation of the findings. The findings show that corporate dominance in Germany is decentralised. Centres with relative corporate dominance tend to host a higher proportion of public limited companies, more companies with a turnover of over one billion Euros and a higher proportion of companies that were founded after the year 2000 than the average German city. The main drivers for recent HQ relocations were corporate restructuring (mergers and demergers) and the centralisation of functions. Furthermore, it has been found that differences in the trade tax burden between municipalities have had no influence on recent relocation decisions within Germany.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses